Patenting and industrial performance: the case of the machine tool industry - Manfred Fleischer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Using the case of an important capital goods industry the paper examines the impact of the national patent system on the performance of firms. Many theories attempt to explain the firms' innovative behavior using the concepts of national and sectorial systems of innovation. The patent law plays a particularly important role in these systems. At the level of the firm its importance rests on the possibility to appropriate profits. An empirical analysis of a sample of the 49 largest international manufacturers of machine tools shows that patents are a superior mechanism for appropriating the returns on R&D in this industry. This is indicated by a strong positive relationship between the market value of the firm and its patenting activities. – – Am Beispiel einer wichtigen Investitionsgüterindustrie wird in diesem Beitrag der Einfluß nationaler Patentsysteme auf den Unternehmenserfolg untersucht. Zahlreiche Theorien gehen davon aus, daß das Innovationsverhalten von Unternehmen von nationalen und sektoralen Innovationssystemen beeinflußt wird. Das Patentrecht spielt in diesen Systemen eine wichtige Rolle. Auf der Unternehmensebene beeinflußt es die Möglichkeiten der Unternehmen Gewinne zu erzielen. Am Beispiel der 49 größten Unternehmen der internationalen Werkzeugmaschinenindustrie wird nachgewiesen, daß in diesem Industriezweig Patente ein wichtiges Instrument zur Erzielung von Gewinnen darstellen. Dies zeigt sich besonders deutlich an der engen positiven Beziehung, die zwischen dem Marktwert der Unternehmen und ihrem Patentierverhalten empirisch festgestellt wurde.
Keywords: 330